Semantic mapping : a visual and structured pre-writing strategy in the process of essay writing / Mah Boon Yih - Mah, Boon Yih (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2011)
Semantic mapping is a kind of graphic organizer. It illustraters a number of approaches designed to demonstrate how key words or concepts are associated to one another through graphic representations. From the previous studies, semantic mapping has demonstrated as a practical teaching and learning technique for students at all grade levels both in regular and remedial classrooms. This method has been identified by researchers as an excellent technique for increasing vocabulary and improving reading comprehension. However, the use of semantic mapping as a writing technique in ESL classroom has been relatively unexplored. The objective of this study is to exemplify the students' feedback during and after the implementation of semantic mapping in the essay writing process. The data was collected via observation and interview. The findings showed positive feedback received from the subjects on the use of semantic mapping in their writing. By using semantic mapping, a slow transition happens from word mapping to sentence production in association with the semantics notions like word association, sense relation, parts of speech, superordination, collocation, and system of logic leading to essay writing.